Biodiversity restated: > 99.9% of global species in Soil Biota - Robert J. Blakemore (ZooKeys)
More than a decade of research led to the conclusion in 2022 that the Soil Biome is home to ~ 2.1 × 1024 taxa and thus supports > 99.9% of global species biodiversity, mostly Bacteria or other microbes, based upon topographic field data. A subsequent 2023 report tabulated a central value of just 1.04 × 1010 taxa claiming soils had 59 ± 15%, i.e., 44–74% (or truly 10–50%?) of the global total, while incidentally confirming upper values of ~ 90% for soil Bacteria. Incompatibility of these two studies is reviewed, supporting prior biodiversity data with the vast majority of species inhabiting soils, despite excluding viruses (now with ~ 5 × 1031 virions and 1026 species most, ~ 80%, in soils). The status of Oligochaeta (earthworms) and other taxa marked “?” in the 2023 paper are clarified. Although biota totals are increased considerably, inordinate threats of topsoil erosion and poisoning yet pertain with finality of extinction. Species affected include Keystone taxa, especially earthworms and microbes, essential for a healthy Soil foundation to sustain the Tree-of-Life inhabiting the Earth.